Impact of Digital Literacy and Problematic Smartphone Use on Life Satisfaction: Comparing Pre- and Post-COVID-19 Pandemic - Busra Taskin; Chiho Ok (MDPI AG, 2022)
Although the impact of digital literacy (DL) and problematic smartphone use (PSU) on life satisfaction was verified in previous literature, little is known about how the impact of two given variables can be differentiated during the COVID-19 pandemic situation. Thus, the purpose of this study was to empirically analyze whether the influence of DL and PSU on life satisfaction has changed as a consequence of the COVID-19 pandemic. We applied a cross-sectional study design to analyze data obtained from a nationwide survey on smartphone overdependence conducted in 2019 and 2020 by the South Korean Ministry of Science and ICT and the National Information Society Agency. Large-scale data obtained from 41,883 individuals were analyzed using hierarchical regression analysis. The results show that the positive relationship between digital literacy and life satisfaction was further strengthened post-COVID-19 rather than pre-COVID-19. In addition, the results suggest that the negative relationship between PSU and life satisfaction is further strengthened during post-COVID-19 rather than pre-COVID-19. The findings indicate that the roles of digital literacy and PSU are more important after the COVID-19 pandemic.